Recent advances in 18F radiochemistry: a focus on B-18F, Si-18F, Al-18F, and C-18F radiofluorination via spirocyclic iodonium ylides - Bernard-Gauthier, Vadim; Wängler, Björn (Journal of nuclear medicine, 2018)
Straightforward radiosynthesis protocols for 18F-labeled radiopharmaceuticals are an indispensable but often overlooked prerequisite to successfully perform molecular imaging studies in vivo by PET. In recent years, thanks to the expansion of the 18F chemical toolbox, structurally diverse and novel clinically relevant radiopharmaceuticals have been synthesized with both high efficiency and ready implementation. This article provides an overview of recent 18F-labeling methodologies, specifically for B-18F, Si-18F, Al-18F, and iodine (III)-mediated radiofluorination via the spirocyclic iodonium ylide technology.